Acute Radiation Oedema of Perithyroid Tissues — A Serious Complication of the Treatment of Thyroid Disorders with High Doses of Radioiodine - Höschl, R.; Nemec, J.; Šilink, K.; Kubal, J. (Nuklearmedizin - NuclearMedicine, 1965)
17 cases with soft tissue oedema developing early after radioiodine treatment of thyroid cancer are described. The typical clinical picture of this complication of radioiodine treatment consists of a sudden rapidly increasing swelling of soft perithyroid tissues during the first 48 hours after the dose administration. The swelling is accompanied by serious breathing distress, most probably as a result of submucosal tissue oedema in the upper respiratory tract. This syndrom is believed to be a life-threatening clinical entity complicating the early course of radioiodine treatment of thyroid cancer, and differing from radiation thyroiditis. In the literature two similar cases were found. The incidence of perithyroid oedema in our patients was 13.2%. Perithyroid oedema occurred usually after large single doses but was not predictable. The possible preventive measures and therapeutic effect of corticoids as life-saving treatment are pointed out.